(untitled) (Bangladesh Journal of Botany, 2021)
In order to provide scientific basis for landscaping of square in Mudanjiang city, the rationality of plant application in 14 urban squares was analyzed by 10/20/30 “rule of thumb” states. The results showed that there were 38 common species which belonged to 15 families and 28 genera. The relative abundances of the most common species, genera and families were 39.8, 43.2 and 49.1%, respectively, which were all higher than the standard of 10/20/30 “rule of thumb” states, indicating that there was still some unreasonable phenomena in the square greening. The plant diversity index was quite different, and the Marglef index and Shannon-Wiener index were positively correlated with the square area and green area. The Pielou index had a positive correlation with the distance and a negative correlation relationship with the green rate. Bangladesh J. Bot. 50(2): 277-287, 2021 (June)